2006
DOI: 10.1111/j.1600-0420.2006.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography versus automated perimetry for follow‐up of optic neuritis

Abstract: ABSTRACT.Purpose: To evaluate the usefulness of optical coherence tomography (OCT) for follow-up of optic neuritis (ON) compared with subjective visual function tests. Methods: Twelve patients with ON underwent a complete ophthalmological evaluation at initial diagnosis, including best corrected visual acuity (VA), visual fields testing and OCT examination. These examinations were repeated periodically over 6 months. Retinal nerve fibre layer (RNFL) thickness evolution was analysed and correlated with VA and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 15 publications
4
75
2
4
Order By: Relevance
“…These OCTs offer faster scan speed and higher image resolution for RNFL imaging than conventional time-domain OCT. 2 Several studies have focused on the measurements and reproducibility of RNFL thickness using Stratus-OCT after optic neuritis (ON) and multiple sclerosis (MS). [3][4][5][6][7][8][9][10][11][12][13] In fact, lower RNFL values correlate with impaired visual function. OCT is a promising tool for evaluating atrophy in patients with ON and MS, and it could evolve into an important primary or secondary outcome measure for MS clinical trials and patient care.…”
Section: Introductionmentioning
confidence: 99%
“…These OCTs offer faster scan speed and higher image resolution for RNFL imaging than conventional time-domain OCT. 2 Several studies have focused on the measurements and reproducibility of RNFL thickness using Stratus-OCT after optic neuritis (ON) and multiple sclerosis (MS). [3][4][5][6][7][8][9][10][11][12][13] In fact, lower RNFL values correlate with impaired visual function. OCT is a promising tool for evaluating atrophy in patients with ON and MS, and it could evolve into an important primary or secondary outcome measure for MS clinical trials and patient care.…”
Section: Introductionmentioning
confidence: 99%
“…However, correlation between RNFL thickness at 1.5 months and BCVA at six months was statistically insignificant. Correlations between RNFL thickness and BCVA, perimetry have been described in patients with ON with [10][11][12] and without [13] multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…They observed significant average RNFL loss -20.38 µm in MSON eyes (95% CI, -22.86 to -17.91). RNFL thickness in eyes affected by ON 59.79 µm-85 µm and in fellow eyes 82.73 µm-99 µm [12,21,[25][26] . In ON without evidence of MS, Costello et al [5] demonstrated RNFL thickness in affected and fellow eyes were 77.5 µm and 99.88 µm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that OCT-measured RNFL values are reduced after ON and that the extent of the RNFL atrophy correlates with diminished visual and neurological function scores. [9][10][11][12][13] Another study has reported that neuronal loss in the macular retinal ganglion cell-inner plexiform layer (GCIPL) is strongly related to visual function and vision-related quality of life in MS patients, and is observed with and without a history of acute ON. 4 A recent study reported that quantifying GCL thickness after acute ON provides opportunities for monitoring early axonal loss and ONto-MS progression in early ON.…”
Section: Introductionmentioning
confidence: 99%